The importance of magnetizing irrigation water for Deglet Nour date palms in sandy soils - Benaichi, Souraya.; Messaoudi, Mohammed; Ghemam Amara, Djilani; Benouamane, Ourida; Zeid,Alia (Occidental Marco Polo, Hammamet, Tunisia, 2025)
The date palm (Phoenix dactylifera L.) is a crucial component of the ecological balance in oases and is also highly significant in the economic sector (OUCIF K. M. T, 2017). Water is a limiting factor for the development of oasis agriculture. Water use efficiency needs to be improved by exploring various irrigation strategies. (Ahmed Sabri and al) Due to soil salinization and water salinity in the Oued Souf region, we conducted an experiment using magnetized water to reduce the effects of soil and water salinity, improve water and nutrient absorption, reduce salt accumulation in the root zone (rhizosphere), and enhance both the quantity and quality of dates الملخص يُعد نخيل التمر (Phoenix dactylifera L.) مكونًا أساسيًا في تحقيق التوازن البيئي داخل النظم الواحية، كما يحظى بأهمية اقتصادية بالغة في العديد من المناطق (OUCIF K. M. T، 2017). وتُعد ندرة المياه من أبرز العوامل التي تحد من تطوير الزراعة في الواحات، مما يستلزم تحسين كفاءة استخدام المياه من خلال دراسة واعتماد استراتيجيات ريّ مبتكرة (Ahmed Sabri وآخرون). وبالنظر إلى مشكلات ملوحة التربة والمياه في منطقة وادي سوف، تم إجراء تجربة باستخدام المياه الممغنطة، بهدف الحد من آثار الملوحة، وتحسين امتصاص المياه والعناصر الغذائية، والحد من تراكم الأملاح في منطقة الجذور (الرايزوسفير)، مع تعزيز كل من إنتاجية وجودة ثمار التمر.
Intervention
Keywords: خيل التمر; الزراعة الواحية; ملوحة المياه; المياه الممغنطة; كفاءة الري; Date palm; Oasis agriculture; Water salinity; Magnetized water; Irrigation efficiency